Answer:
24ab-8ac
Step-by-step explanation:
Assuming you want to simplify it.
Original equation: 8a(3b+6c-7c)
Apply 8a to each variable in the paranthesis: (8a)(3b)+(8a)(6c)+(8a)(-7c)
After multiplication: 24ab+48ac-56ac
Combine like terms: 24ab-8ac
Answer:
-11
3
5
-24
Step-by-step explanation:
We know that
1 Kg is equals to--------------> 1000 g
so
X Kg------------------------> 300 g
X=300/1000------> x=0.30 Kg
if 2 Kg cost--------------> <span>£7.20
0.30 Kg-------------> X
X=0.30*7.20/2------> x=1.08
the answer is
</span>£1.08
Answer:
2.2
Step-by-step explanation: